2021
DOI: 10.26686/wgtn.14910162.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Professional Development Experiences Of English As A Foreign Language Lecturers At A Vietnamese University

Abstract: <p><b>As a consequence of globalisation, English language teaching (ELT) has been identified as one of the key emphases of the national education reforms in Vietnam. Professional development (PD) of teachers attempts to enhance the quality of ELT. However, there is a paucity of research investigating English as a foreign language (EFL) lecturers’ perceptions towards their experiences of PD in order to understand how PD currently functions and could potentially function within the context of Vietnam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 130 publications
1
4
0
Order By: Relevance
“…The findings of this study also indicate that the teachers were active and dynamic subjects of their PD activity. This is consistent with the findings by Dau (2020), Ngo (2021), Phan (2017) regarding the activeness of teachers in PD. Nguyen and Bui (2016), in their study of teachers' agency and enactment of educational reform in Vietnam, also concluded that "teachers are highly capable of exercising their agency as comprehensive policy implementers" (p. 88).…”
Section: Power and Agencysupporting
confidence: 93%
See 4 more Smart Citations
“…The findings of this study also indicate that the teachers were active and dynamic subjects of their PD activity. This is consistent with the findings by Dau (2020), Ngo (2021), Phan (2017) regarding the activeness of teachers in PD. Nguyen and Bui (2016), in their study of teachers' agency and enactment of educational reform in Vietnam, also concluded that "teachers are highly capable of exercising their agency as comprehensive policy implementers" (p. 88).…”
Section: Power and Agencysupporting
confidence: 93%
“…First, this may have occurred because they were active participants who wanted sufficient information to make up their minds on whether the CoP suited them. This is supported by Ngo's (2021) study which showed that EFL teachers are active, not passive participants with their PD opportunities. They actively chose to attend PD programmes that met their needs.…”
Section: Effective Communicationmentioning
confidence: 65%
See 3 more Smart Citations